2022
DOI: 10.31098/orcadev.v1i1.868
|View full text |Cite
|
Sign up to set email alerts
|

Employee Workload Assessment in The Service and Manufacturing Industry

Abstract: In the face of the COVID-19 pandemic, the industry has implemented new policies in managing its workforce, one of which is by reducing employees. The reduction of employees in the industry causes an excessive workload on several work units in the industry, both the service industry and the manufacturing industry. To perform better manpower management, management in the industry needs to know the workload of employees in each work unit. This is quantitative research by taking a case study of one sample of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…It serves as a bridge by assisting workers in the design of their work, the recruitment and selection of the best candidates for open positions, and the training and development of workers as a crucial element of the workplace (Armstrong & Taylor, 2023). Accordingly, the primary goal of human resources management is to utilize the available people in this system in the most productive and effective manner possible in order to achieve the desired results (Pramestari et al, 2022). Faisal (2023) additionally, improving organizational effectiveness and employee job satisfaction is also taken into account in the context of this goal.…”
Section: Human Resources Managementmentioning
confidence: 99%
“…It serves as a bridge by assisting workers in the design of their work, the recruitment and selection of the best candidates for open positions, and the training and development of workers as a crucial element of the workplace (Armstrong & Taylor, 2023). Accordingly, the primary goal of human resources management is to utilize the available people in this system in the most productive and effective manner possible in order to achieve the desired results (Pramestari et al, 2022). Faisal (2023) additionally, improving organizational effectiveness and employee job satisfaction is also taken into account in the context of this goal.…”
Section: Human Resources Managementmentioning
confidence: 99%
“…The association between training experiences and attitudes is investigated in this study. This study investigates the associations between training experiences, attitudes, and perceptions of work proficiency (Pramestari, Henni, & Novrigent, 2022). Faisal (2023) demonstrated that there is almost no direct evidence regarding firm training strategies based on representative samples of various employing organizations.…”
Section: Figure 1: Source: Maxqda 2020 Output 2023mentioning
confidence: 99%
“…Penting untuk mengelola beban kerja dengan bijaksana, karena beban kerja yang berlebihan dapat menyebabkan stres, kelelahan, dan bahkan penurunan produktivitas (Biondi et al, 2021). Sebaliknya, beban kerja yang terlalu ringan juga dapat mengakibatkan kurangnya pemanfaatan potensi dan kemampuan karyawan (Pramestari et al, 2022). Dengan mendistribusikan beban kerja secara adil dan sesuai kemampuan, rumah makan dapat mencapai keseimbangan yang baik antara efisiensi dan kesejahteraan karyawan, sehingga meningkatkan kinerja dan keberhasilan dalam mencapai tujuan rumah makan (Priyono & Suhariadi, 2021).…”
Section: Pembahasanunclassified